82.4k views
4 votes
Solve this system of equations using the elimination method.

6x + 2y = 18
-4x - 2y = -6
( ? , ? )

User Detilium
by
5.3k points

2 Answers

2 votes

Answer:

(6,-9)

Explanation:

6x + 2y = 18

-4x - 2y = -6

2y = -4x + 6

6x - 4x + 6 = 18

2x = 12

x = 6

2y = -4(6) + 6

2y = -18

y = -9

(6,-9)

User Henry Dang
by
4.6k points
7 votes

Answer:

(6, -9)

Explanation:

Our system of linear equations is:

6x + 2y = 18

-4x - 2y = -6

When we solve by elimination, we're essentially "eliminating" a variable so that we can solve for other more easily. Here, let's eliminate the y variable by adding the two equations together:

6x + 2y = 18

+ -4x - 2y = -6

____________

2x + 0y = 12

x = 12/2 = 6

Plug this back into one of the original equations to find y:

-4x - 2y = -6

-4 * 6 - 2y = -6

-24 - 2y = -6

-2y = 18

y = -9

The solution is (6, -9).

User Satys
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.